Measuring the prevalence of open access in Canada: A national comparison - Paquet, Virginie; van Bellen, Simon; Larivière, Vincent (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie, 2022)
For two decades, open access (OA) has gained momentum worldwide. However, adoption of OA in Canada is lagging compared with other countries. Using data from Dimensions and Érudit, this paper provides an overview of OA dissemination in Canada, focusing on the effect of institutions, language, and funding. Papers in French, and from Quebec universities, are more likely to be OA, while papers from engineering-oriented institutions are less likely to be OA. Regarding funders, those in health sciences have higher OA compliance. The paper concludes discussing disciplinary differences in OA dissemination, low compliance to OA mandates in Canada, and the role of Érudit.